Faktor-Faktor yang Berhubungan dengan Kejadian Kala II Memanjang - Imas Nurjanah; Nurul Azmi Fauziah; Anzhany Putri Feidha; Nadya Rismana Fitriani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The duration of the second stage of labor is a significant factor influencing maternal and neonatal outcomes. Maternal and neonatal mortality rates remain a major global health challenge, and various risk factors, including prolonged second stage of labor, contribute to this issue. Successful childbirth is influenced by risk factors such as maternal age, parity, and body mass index (BMI). This cross-sectional study aimed to analyze the relationship between maternal age, parity, and BMI on the duration of the second stage of labor among 224 postpartum women at TPMB M in 2023. The results showed that women with advanced maternal age (<20 years or >35 years), nulliparity or grand multiparity, and underweight or obese BMI were at significantly higher risk of prolonged second stage of labor. These findings highlight the need for special attention to pregnant women with these risk factors to prevent obstetric complications. Healthcare providers are encouraged to enhance risk factor monitoring through education, screening, and comprehensive management during pregnancy.